2014
DOI: 10.3109/09286586.2014.903981
|View full text |Cite
|
Sign up to set email alerts
|

Barriers for Poor Cataract Surgery Uptake among Patients with Operable Cataract in a Program of Outreach Screening and Low-cost Surgery in Rural China

Abstract: The principal barriers to low-cost cataract surgery uptake in rural China included lack of family support and failure to understand the need for surgery. Education targeting entire families to eliminate these barriers and development of community support systems at the family level are required to achieve greater uptake of low-cost cataract surgery programs in rural China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 24 publications
2
27
0
Order By: Relevance
“…17,[19][20][21][22][23] Quality of cataract surgery also remains a concern, with poor outcomes reaching 40% in some places. 24 In fact, many ophthalmologists do not perform surgery or may be inadequately trained.…”
Section: à50mentioning
confidence: 99%
“…17,[19][20][21][22][23] Quality of cataract surgery also remains a concern, with poor outcomes reaching 40% in some places. 24 In fact, many ophthalmologists do not perform surgery or may be inadequately trained.…”
Section: à50mentioning
confidence: 99%
“…[1][2][3][4][5][6] In the hands of a capable surgeon, cataract surgery can result in good vision [7][8][9] and patient satisfaction 10 at least 90% of the time, and recent studies have shown that these operations can transform the economic outlook of patients and families. [10][11][12][13] It is thus particularly disturbing that patients with visually significant cataract refuse free or low-cost surgery in some 80% of cases, as documented in papers by Kovai and co-workers 14 and Zhang and co-workers 15 in the current issue.…”
mentioning
confidence: 83%
“…14,15 Another paper in the current issue by Li and colleagues 16 reporting population-based cataract surgical outcomes in China suggests fear over bad results may be justified: only a third of patients had postoperative visual acuity 46/ 18, and nearly a third had56/60. Despite some trends towards improvement with wide adoption of intraocular lens surgery, larger population-based studies in China 17 and those from elsewhere in Asia 18,19 report similar results.…”
mentioning
confidence: 94%
See 2 more Smart Citations